2018
DOI: 10.1093/ejo/cjy003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of biologic factors and adjunctive therapies on orthodontically induced inflammatory root resorption: a systematic review and meta-analysis

Abstract: In animals, administration of fluoride, thyroxine and steroids decreased OIIRR, whereas corticotomy increased OIIRR. In general, the effect on OIIRR increased with higher dosage and/or exposure time. Despite methodological limitations of the included studies, this systematic review provides an important overview of the effect of biologic factors and adjunctive therapies on OIIRR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 58 publications
0
12
1
Order By: Relevance
“…Results of the current study demonstrated that MOP neither increased nor decreased root resorption, in contrast to a recent systematic review which accused corticotomy of increasing the orthodontically induced root resorption [31].…”
Section: Discussioncontrasting
confidence: 99%
“…Results of the current study demonstrated that MOP neither increased nor decreased root resorption, in contrast to a recent systematic review which accused corticotomy of increasing the orthodontically induced root resorption [31].…”
Section: Discussioncontrasting
confidence: 99%
“…OIIRR is a common complication of orthodontic treatment, 22 which can be induced by the application of heavy orthodontic force, injury to moving teeth, metabolic diseases, traumatic occlusion, 23 and other causes (e.g., systemic conditions, 24 malocclusion type, 25 or treatment period 26 ). OIIRR is an inflammatory response characterized by the periodontal accumulation of many proinflammatory cytokines released from migrated cells and paradental resident cells, including TNF-α, interleukin-1β, interleukin-6, interleukin-7, interleukin-8, prostaglandin E2, and cyclooxygenase-2.…”
Section: Discussionmentioning
confidence: 99%
“…Several pharmacological agents (e.g., prostaglandin E2, zoledronate, alendronate, and fluoride) may prevent root resorption; however, the clinical applications of these agents are limited because they have adverse effects on orthodontic tooth movement. 2 4 Previous studies have shown that low-intensity pulsed ultrasound reduces the severity of OIIRR and promotes cementum repair by enhancing alkaline phosphatase activity, collagen-I synthesis, and runt-related transcription factor 2 (Runx-2) protein levels in cementoblasts. 5 , 6 However, extensive exposure to low-intensity pulsed ultrasound can cause occasional degeneration and fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of one Cochrane review 18 concluded that there was very little clinical research concerning the effectiveness of non‐surgical interventions on accelerating treatment during orthodontic treatment using fixed appliances. Hougland et al 19 evaluated the effect of biologic factors and adjunctive therapies on OIIRR; however, they included only those studies with fixed appliances. They assessed only 3 clinical studies on adjunctive interventions.…”
Section: Introductionmentioning
confidence: 99%